Perlindungan Hak Pekerja Atas Harta Pailit Yang Berupa Jaminan Pihak Ketiga (Studi Kasus Putusan Nomor 37/PDT.SUS.GLL/2019/PN.NIAGA.JKT.PST) - Nur Afni (Jurist-Diction, 2022)
AbstractA bankruptcy decision on a company can result in termination of employment. In bankruptcy, there are three types of creditors, namely preferred creditors, separatist creditors and concurrent creditors. Workers as preferred creditors in the law shall prioritize the distribution of wages owed. However, the position of workers is often ignored and gives priority to payment to separatist creditors. This is because separatist creditors can execute collateral objects and the proceeds are not shared with preferred creditors. Moreover, if the bankruptcy estate is in the form of collateral belong to a third party, the holder of the guarantee is the creditor. Other creditors do not receive a share because they are not entitled to collateral that belongs to a third party, which is not included in the debtor's bankruptcy estate. Workers are not entitled to third party guarantees, but workers get their rights from the board of directors. The Board of Directors is responsible for the company's debt that has not been paid by placing the money in bankrupt assets. It is the board of directors responsibility for negligence in controlling the company which resulted in bankruptcy.Keywords: Bankruptcy; Workers; Collateral; Third Parties.AbstrakPutusan pailit pada perusahaan dapat berakibat adanya pemutusan hubungan kerja. Dalam kepailitan terdapat tiga jenis kreditor yakni kreditor preferen, kreditor separatis dan kreditor konkuren. Pekerja sebagai kreditor preferen dalam Undang-Undang pembagiannya diadahulukan atas upah terutang. Akan tetapi kedudukan pekerja sering dihiraukan dan lebih mengutamakan pembayaran pada kreditor separatis. Karena kreditor separatis dapat melakukan eksekusi benda jaminan dan hasilnya tidak dibagikan kepada kreditor preferen. Terlebih lagi jika harta pailit tersebut berebentuk jaminan milik pihak ketiga maka yang menguasai atas jaminan tersebut yakni kreditor pemegang. Untuk kreditor lainnya tidak mendapat pembagian karena tidak berhak atas jaminan milik pihak ketiga, yang mana bukan termasuk dari harta pailit debitor. Pekerja tidak berhak atas jaminan milik pihak ketiga tetapi pekerja mendapatkan haknya dari direksi. Direksi bertanggung jawab atas utang perusahaan yang belum dibayarkan dengan memasukkan uangnya ke harta pailit. Sebagai tanggung jawab direksi atas kelalaiannya dalam pengendalian perusahaan sampai mengakibatkan pailit.Kata Kunci: Kepailitan; Pekerja; Jaminan; Pihak Ketiga.